A study of factors causing math anxiety among undergraduate students - Zanabazar, Altanchimeg; Deleg, Amartuvshin; Ravdan, Magsar (International Journal of Innovative Research and Scientific Studies, 2023)
Mathematics is a subject with numerous applications in everyday life but it is often viewed as difficult leading to math anxiety among students. This anxiety can limit students' career options and affect their success. To address this issue, we investigated the factors contributing to math anxiety among university and college students. This study focused on students from the National University of Mongolia (NUM) and the Mongolian State University of Education (MSUE). We used the Mathematics Anxiety Rating Scale questionnaire (A-MARS) developed in 1972 by Richardson and Suinn and conducted various statistical tests including factor analysis, correlation analysis and regression analysis to analyze the data. Our results show that teacher-related factors have a strong negative correlation with math anxiety (β=-0.583) while family-related factors (β=-0.311) and student-related factors (β=-0.133) have weaker correlations. Possible explanations for these findings include inadequate teaching and professional skills, poor communication between students and teachers, heavy task loads and outdated resources. This study highlights the importance of these factors to reduce math anxiety and promote success in mathematics education.